2012
DOI: 10.1007/s10695-012-9736-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azadirachtin on haematological and biochemical parameters of Argulus-infested goldfish Carassius auratus (Linn. 1758)

Abstract: Argulosis hampers aquaculture production and alters the host physiology and growth. Azadirachtin is recognized as a potential antiparasitic agent against Argulus sp. The present study aimed to investigate the effect of different concentration of azadirachtin solution on haematological and serum biochemical parameters of Argulus-infested goldfish Carassius auratus. Ninety Argulus-infested goldfish were randomly divided into six equal groups. Fish of group 1-5 were treated with azadirachtin solution through bath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 48 publications
6
46
1
Order By: Relevance
“…Thus, decrease of serum BUN concentration of surfactin supplementation groups might suggest a potential enhancement of synthesis of protein in animals ). The increased activity of AST and ALT in serum, in the absence of acute necrosis or ischaemia of other organs such as myocardium, suggests liver cell damage and leaching of these enzymes in blood (Kumar et al 2013). The lower levels of AST and ALT of surfactin supplementation groups in this study indicated that tilapia hepatopancreas might have better health status.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, decrease of serum BUN concentration of surfactin supplementation groups might suggest a potential enhancement of synthesis of protein in animals ). The increased activity of AST and ALT in serum, in the absence of acute necrosis or ischaemia of other organs such as myocardium, suggests liver cell damage and leaching of these enzymes in blood (Kumar et al 2013). The lower levels of AST and ALT of surfactin supplementation groups in this study indicated that tilapia hepatopancreas might have better health status.…”
Section: Discussionmentioning
confidence: 59%
“…However, the threat of bioaccumulation in the host, caused by the frequent use of these drugs, reduces sensitivity of the Argulus to the organophosphate dichlorvos (Jones et al 1992) and has forced to find alternative control methods (Goven et al 1980;Klinger and Floyd 2002). Recently, phytotherapeutants such as azadirachtin (Kumar et al 2012a, b;Banerjee and Saha 2013), piperine (Kumar et al 2013), rotenone and nicotine (Banerjee and Saha 2013) have been documented as a biodegradable and cheap herbal extracts to combat Argulus infections. However, easy unavailability of pure extracts or synthetic substitutes, the intricate pharmacodynamics with water, their potential for toxicity at higher doses and the rapid disintegration of some bioactive molecules in the phytotherapeutants make their use difficult in large aquaculture systems (Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of Rao and Chakrabarti 70 , Catla catla fed with Achyranthes aspera diet for four weeks showed resistance against bacterial pathogens elucidating that immunostimulant at an optimal dose, could enhance the resistance of fish against aquatic pathogens. Kumar et al 20 reported higher survival percentage in azadirachtin fed C. auratus exposed to A. hydrophila. Similar findings were also reported by Kaleeswaran et al 64 who fed Cynodon dactylon mixed diet to C. catla.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing interest in the modulation of fish innate immune system as a preventive measure against disease outbreak has led to the use of plant materials as feed supplement. Herbal extracts are used in fish culture as an alternative for chemotherapeutic agents [18][19][20] . Plant extracts have been reported to enhance activities like appetite stimulation, growth promotion, immunostimulation, anti-microbial properties in fish aquaculture due to active principles as alkaloids, terpenoids, tannins, saponins, falvonoids, phenolics, steroids or essential oils 21,22 .…”
Section: Introductionmentioning
confidence: 99%